Characterization and Biological Activities of Protein-Bound Polysaccharides Produced by Cultures of Pleurotus ostreatus - Salvador, C (2013)
Abstract: Several species of mushrooms, as Pleurotus ostreatus, have been valued as edible and medicinal resources. These mushrooms may be an important source of polysaccharides with medicinal properties as antioxidant, antitumoral, antimicrobial and immunological properties. The aim of this work was to produce and to evaluate the biological properties of protein-bound polysaccharide complexes, extra intracellular (E-PPS and I-PPS), extracted from P. ostreatus cultures, using agricultural sunflower wastes as carbon source. Three main compounds in the E-PPS and four main compounds in the I-PPS were identified by SEC-UV-RI-HPLC. These complexes of P. ostreatus present no toxicity in Artemia salina cultures, after 24 h of incubation. Antioxidant properties of the complexes were evaluated by radical scavenging activity using DPPH method and lipid peroxidation inhibition capacity, determined by erythrocytes hemolysis. Additionally, E-PPS and I-PPS extracts revealed capacity to mimetize superoxide dismutase and catalase enzymatic activities. The hepatoprotector effect of E-PPS extracts in Wistar rats was evaluated by AST, ALT, ALP and γ-GT activities, showing capacity to reduce the liver damage induced by ethanol-administration. This hepatoprotective effect is equivalent to that observed by silymarin, a standard drug. Our results suggests that the extracts of E-PPS and I-PPS produced by P. ostreatus cultures, using agricultural sunflower wastes as main carbon source, can be used as an important source of bioactive compounds with potential medicinal value.